Taste as experience : the philosophy and aesthetics of food - Perullo, Nicola, 1970- (Arts and traditions of the table., 2016)
"Taste as Experience puts the pleasure of food at the center of human experience. It shows how the sense of taste informs our preferences for and relationship to nature, pushes us toward ethical practices of consumption, and impresses upon us the importance of aesthetics. Eating is often dismissed as a necessary aspect of survival, and our personal enjoyment of food is considered a quirk. Nicola Perullo sees food as the only portion of the world we take in on a daily basis, constituting our first and most significant encounter with the earth. Perullo has long observed people's food practices and has listened to their food experiences. He draws on years of research to explain the complex meanings behind our food choices and the thinking that accompanies our gustatory actions. He also considers our indifference toward food as a force influencing us as much as engagement. For Perullo, taste is value and wisdom. It cannot be reduced to mere chemical or cultural factors but embodies the quality and quantity of our earthly experience."--Publisher's description